Psalm 133: Ancient Wisdom Interpreted by Contemporary South Africans - Dickie, June F. (Journal for Semitics, 2020)
This short psalm is generally regarded as a wisdom psalm, celebrating family and community. In biblical times it may have served to encourage fellowship among pilgrims travelling to Jerusalem for the feasts, or as a call for unity among the northern and southern tribes. But how is it interpreted today? Does it speak to our social relations? For this article, three groups of contemporary South Africans study the psalm and share their perceptions as to its meaning for them. The groups include women in a township who are part of a church “home-group”, teenagers from various backgrounds who attend a weekly “youth meeting” at a local church, and performance artists who are members of the same church. Each group shows imaginative ideas and significant engagement with the psalm. The study contributes by showing that the ancient wisdom in the psalm is meaningful today although the imagery and media may need to be adjusted to the particular audience. It is thus a stimulus to those who work with young people to encourage them to “re-translate” biblical texts (particularly poems) and thus to make them their own.
free
Keywords: community; creative arts; psalms; translation; unity; youth